Make an impact with your written English how to use word power to impress in presentations, reports, PR and meetings - Talbot, Fiona (London Philadelphia Kogan Page, 2009)
This volume in the "Better Business English" series focuses on presentations, reports, note-taking, PR writing, technical writing, and writing for the web.? Make an Impact with Your Written English helps non-native speakers write business English in a confident and competent voice.
Half title page; Title page; Copyright; Dedication; Table of contents; Preface; Introduction; Chapter 1 Writing English for business; Chapter 2 Deciding your business writing objectives; Chapter 3 Reading and writing challenges and needs; Chapter 4 Writing for presentations and talks; Chapter 5 We all need to write to market and sell; Chapter 6 Making an impact through written word power; Chapter 7 Four steps to success; Chapter 8 Writing press releases and editorial; Chapter 9 Writing reports; Chapter 10 Writing agendas, meeting notes and minutes; Chapter 11 Word Power Skills 2.0; Conclusion.
Electronic reproduction.
Keywords: English language -- Business English -- Study and teaching; Business communication; Business writing; Electronic books